2018
DOI: 10.1155/2018/6496379
|View full text |Cite
|
Sign up to set email alerts
|

Study on Force Schemes in Pseudopotential Lattice Boltzmann Model for Two-Phase Flows

Abstract: Multiphase flows are very important in industrial application. In present study, the force schemes in the pseudopotential LBM for two-phase flows have been compared in detail and the force schemes include Shan-Chen, EDM, MED, and Guo's schemes. Numerical simulations confirm that all four schemes are consistent with the Laplace law. For Shan-Chen scheme, the smaller is, the smaller the surface tension is. However, for other schemes, has no effect on surface tension. When 0.6 < ≤ 1, the achieved density ratio wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Those data were classified according to two categories, air and water signals. The air concentration ( C ) was computed as the encountering air's probability at the leading tip of the probe, which can be expressed as [26]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those data were classified according to two categories, air and water signals. The air concentration ( C ) was computed as the encountering air's probability at the leading tip of the probe, which can be expressed as [26]…”
Section: Methodsmentioning
confidence: 99%
“…A simplified analogy would be to consider on aeration flows past a fixed probe, as a series of discrete one-dimensional air and water The number of data (N) can be obtained by multiplying the frequency (f ) of the measurement instrument with the sampling time T, i.e., N = f × T. Those data were classified according to two categories, air and water signals. The air concentration (C) was computed as the encountering air's probability at the leading tip of the probe, which can be expressed as [26]…”
Section: Air Bubble Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of computer technology, numerical methods have been applied more and more to complex flows of industrial relevance [25][26][27][28][29][30]. The most widely used approach in both academia and industry for the modeling of turbulent flows is Reynolds-averaged Navier-Stokes (RANS) methods that solve additional transport equations for turbulence and introduce the turbulence eddy viscosity to simulations to mimic the effect of turbulence.…”
Section: Turbulence Modelmentioning
confidence: 99%
“…Physical models were established by Zhang and Chanson [11] to examine the effect of step edge and cavity geometry on the air entrainment and energy loss performance in stepped chutes. Apart from experimental studies, thanks to the advances in the computational performance of computers, numerical methods have also been successfully used to study the detailed flow properties in complex contexts [12][13][14][15]. Baylar et al [16] numerically examined the energy loss and aeration efficiency of the stepped chutes and found that both of them in nappe flow regime were greater than that of the skimming flow regime.…”
Section: Introductionmentioning
confidence: 99%